2015
DOI: 10.1002/app.42176
|View full text |Cite
|
Sign up to set email alerts
|

Depolymerization of renewable resources—lignin by sodium hydroxide as a catalyst and its applications to epoxy resin

Abstract: Alkali lignin was successfully depolymerized into polyols with high hydroxyl number via direct hydrolysis using sodium hydroxide (NaOH) as a catalyst, without any organic solvent agent. Hydrolysis of lignin can produce a multitude of high-value products via alkali-catalyzed cleavage. This process usually gives good results with respect to the yield of phenols. Through this method, the numbers of the hydroxymethyl and phenolic hydroxyl groups of lignin had been dramatically increased, reaching 2.11%, nearly fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Chen et al [ 65 ] prepared the polyols-like depolymerized lignin (DL) with high hydroxyl content by depolymerizing alkali lignin at the optimized NaOH concentration (15 wt%) and temperature (250 °C). They reported that this method increases the –OH group, about 2.11% in DL, and reduces environmental pollution.…”
Section: Lignin-based Resinsmentioning
confidence: 99%
“…Chen et al [ 65 ] prepared the polyols-like depolymerized lignin (DL) with high hydroxyl content by depolymerizing alkali lignin at the optimized NaOH concentration (15 wt%) and temperature (250 °C). They reported that this method increases the –OH group, about 2.11% in DL, and reduces environmental pollution.…”
Section: Lignin-based Resinsmentioning
confidence: 99%
“…In base-catalyzed depolymerization, the choice of lignin influences the yield of bio-oil, but not the resulting composition [59]; however, the use of mineral bases may necessitate neutralisation of the subsequent bio-oil, in addition to reactor corrosion. Thring et al studied the effect of time and temperature on the depolymerization of Alcell lignin catalyzed by NaOH [57] obtaining guaiacol, syringol, and under certain conditions catechol and its derivatives [57,60,61]. Base-catalyzed depolymerization has proven an effective protocol in polar organic solvents, such as ethanol and methanol, suppressing char formation, and hence enhancing monomer and dimer production relative to solid acid catalysts.…”
Section: Base-catalyzed Depolymerizationmentioning
confidence: 99%
“…The effects were detected using various advanced analysis techniques, including NMR and ultraviolet spectrophotometry, as well as size-exclusion chromatography. By depolymerizing lignin, a decrease in molar mass can be obtained, as well as an increase in the OH ph content [39], which could be favorable for the production of bio-based polymers.…”
Section: Introductionmentioning
confidence: 99%